Disseminated tuberculosis presenting as pneumomediastinum: a case report - Phadte, Aditya Dhananjay; Nayak, Chitralekha Anilkumar; Menezes, Ramona; Naik, Akshay Surendra (International Journal of Research in Medical Sciences, 2018)
This study describes a rare case of a 19 year old girl who presented with features of subcutaneous emphysema and pneumomediastinum to the emergency department in whom further investigation revealed pulmonary and neurotuberculosis. Tuberculosis presenting as pneumomediastinum and subcutaneous emphysema is a rare, but an important entity and a better knowledge of this condition can help in the early diagnosis and adequate management of tuberculosis.